2011
DOI: 10.1007/s00436-011-2513-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma sp. in cattle from Tanzania estimated by conventional PCR and loop-mediated isothermal amplification (LAMP)

Abstract: This study compared the prevalence of trypanosome infections estimated by PFR-loop-mediated isothermal amplification (LAMP) with conventional polymerase chain reaction (PCR) tests. One hundred forty eight cattle blood samples were collected from Robanda village, Mara region, Tanzania in April 2008. In conventional PCR, four sets of primers, specific for the detection of Trypanosoma sp., Trypanosoma brucei rhodesiense, Trypanosoma vivax, and Trypanozoon, as well as a modified LAMP were used. Conventional PCR de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Moreover, microscopic examination of the buffy coat detected five samples that were positive for both T. congolense and T. vivax. This result is consistent with other reports which indicate that co-infection of animal trypanosomosis is present in African cattle (Gillingwater et al 2010;Laohasinnarong et al 2011). Since the therapeutic treatment for different animal trypanosomosis are quite similar, the TeGM6-4r/ICT, which can detect several pathogenic trypanosomes, represents a good choice of test.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, microscopic examination of the buffy coat detected five samples that were positive for both T. congolense and T. vivax. This result is consistent with other reports which indicate that co-infection of animal trypanosomosis is present in African cattle (Gillingwater et al 2010;Laohasinnarong et al 2011). Since the therapeutic treatment for different animal trypanosomosis are quite similar, the TeGM6-4r/ICT, which can detect several pathogenic trypanosomes, represents a good choice of test.…”
Section: Discussionsupporting
confidence: 83%
“…Although trypanosomosis is commonly reported in farm animals, 4 canine African trypanosomosis (CAT) is rarely reported in the literature. 3,5 This communication evaluates the performance of loop-mediated isothermal amplification (LAMP) in detecting CAT from six exotic dogs naturally infected with trypanosomes from Zambia's South Luangwa National Park (SLNP) and Chiawa Game Management Area (CGMA), against routine microscopy.…”
Section: 3mentioning
confidence: 99%
“…In agreement with previous reports, 3 T. congolense-infected dogs tended to exhibit chronic infections unlike those infected with T. brucei subspecies that showed more acute symptoms. Such chronically infected dogs may act as a source of infection to other domestic animals 4 in tsetseinfested regions.…”
Section: 3mentioning
confidence: 99%
“…This technique has been proven to be an accurate, rapid and simple method, which amplifies the target nucleic acid under isothermal conditions (Notomi et al, 2000). Recently, wide applicability of LAMP in the detection of parasitic protozoa such as Babesia, Plasmodium, Leishmania and Trypanosoma in clinical samples has been demonstrated (Ikadai et al, 2004;Poon et al, 2006;Njiru et al, 2008;Takagi et al, 2009;Thekisoe et al, 2007;Laohasinnarong et al, 2011). Studies have also shown the application of LAMP to survey vectors of infectious diseases (Aonuma et al, 2009;Thekisoe et al, 2010;Nakao et al, 2010); however, these studies used purified DNA as a template for the LAMP assays.…”
Section: Introductionmentioning
confidence: 99%